Web-Based 21st-Century Skills-Oriented E-Module for Chemistry Teacher Candidates - Erviyenni; Fitri Aldresti; Sri Haryati (Universitas Pendidikan Ganesha, 2023)
The development of science and technology has brought major changes in the world of education. In the learning process in tertiary institutions, along with the complexity of the problems in learning activities, student competencies are no longer limited to mastery of material content but also need 21st-century competencies. This research was conducted to develop web-based 21st-century oriented e-modules for DDPMIPA lectures that validate and know the response of e-module users. This type of research is developed using the ADDIE model. The data collection method uses a questionnaire. Research data were obtained using e-module validation sheets and user response questionnaires. The material and media expert validators carried out the validation test. The trial was conducted on three students, and the limited trial was conducted on 15 students. Data were analyzed using quantitative descriptive and qualitative descriptive analysis techniques. Based on the results of data analysis, it is known that the e-module is categorized as very valid (88.5%) in terms of content feasibility, presentation feasibility aspects, linguistic aspects, and media eligibility aspects. The user response questionnaire also shows that the e-module gets very good user responses (87.93%). It was concluded that the resulting 21st-century skill-oriented e-modules using Google sites were valid and very good to apply in DDPMIPA learning.